2013
DOI: 10.1002/jor.22418
|View full text |Cite
|
Sign up to set email alerts
|

Improved repair of chondral and osteochondral defects in the ovine trochlea compared with the medial condyle

Abstract: Associations between topographic location and articular cartilage repair in preclinical animal models are unknown. Based on clinical investigations, we hypothesized that lesions in the ovine femoral condyle repair better than in the trochlea. Full-thickness chondral and osteochondral defects were simultaneously established in the weightbearing area of the medial femoral condyle and the lateral trochlear facet in sheep, with chondral defects subjected to subchondral drilling. After 6 months in vivo, cartilage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 47 publications
(114 reference statements)
2
56
0
Order By: Relevance
“…Finally, the different location of the defects in the two animal models (trochlear groove versus femoral condyle) may weaken the algorithm. As cartilage repair differs in the sheep trochlea compared with the medial femoral condyle21, the suggested thresholds for bone cyst and peri-hole resorption may need to be adapted accordingly if the extent and pattern of subchondral bone alterations are similarly topographically dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the different location of the defects in the two animal models (trochlear groove versus femoral condyle) may weaken the algorithm. As cartilage repair differs in the sheep trochlea compared with the medial femoral condyle21, the suggested thresholds for bone cyst and peri-hole resorption may need to be adapted accordingly if the extent and pattern of subchondral bone alterations are similarly topographically dependent.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] As a strategy to regenerate these structures in a layer-by-layer fashion, biphasic or triphasic constructs have been developed due to both mechanical and biological reasons, including the acquisition of initial mechanical strength, mimicking a natural articulate structure, a uniform tidemark at the osteochondral junction, and integration of the biphasic implant with host tissue to sustain biological function. 7,[36][37][38][39][40][41][42][43][44] For satisfying the biological requirements, an osteochondral implant should ideally have a rigid osseous layer (to support the overlying cartilage and integrate with the native bone) and a chondral layer (to enable the seeding and proliferation of chondrocytes or mesenchymal stem cells (MSCs) and subsequent deposition of cartilaginous ECM).…”
Section: Strategy For Osteochondral Repairmentioning
confidence: 99%
“…This destruction is a result of the surgical trauma and compaction of the SCB plate that occurs with penetration of either a microfracture pic or drilling[27]. In the sheep osteochondral lesion model, Orth et al[28] revealed that the SCB plate was not restored at 6 mo after BMS. This finding was supported in the human ankle by Reilingh et al[29] which revealed that the SCB were not filled completely in 78.6% (44 of 58) OLT at 1 year after BMS.…”
Section: Treatmentmentioning
confidence: 99%